Bringing Hardware Multithreading to the Real-Time Domain - Gomes, Tiago (2016)
The emergence of hardware multithread (HW-MT) architectures increased the performance of MT applications. However, traditional HW-MT architectures are not suitable to real-time operating systems as their performance-oriented scheduling algorithm may conflict with RTOS software scheduling. This letter presents RT-SHADOWS, a portable architecture which provides a unified hardware-software scheduling, bringing the benefits of HW-MT to the RTOS domain. We show that tightly-coupled real-time compliant hardware integration achieves throughput benefits, maintaining the RTOS scheduling policy intact while increasing the predictability of RTOSes. Our solution shows on average, speed-ups between 3 and 4 times over the native versions with very low area usage/performance overhead ratio, due to its minimal cost (2% of extra slices per hardware-supported thread). This work surpasses related work by providing a complete and agnostic hardware solution which is independent of any specific RTOS.